PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT SIANTAR TOP BEKASI - Andre Setiawan; Hotma Napitupulu; Tini Juartini (Jurnal Ekonomi dan Industri, 2025)
To determine the influence of organizational culture and competency on employee performance at PT Siantar Top Bekasi. In this research, the sampling technique used is based on the population, using saturated samples or total sampling. Data collection uses survey techniques via questionnaires. Analysis method using multiple and simple linear regression. The research results can be found, namely: that organizational culture and competency simultaneously and simple had a positive and significant effect on employee performance at PT Siantar Top Bekasi.